2007
DOI: 10.1037/1091-7527.25.4.404
|View full text |Cite
|
Sign up to set email alerts
|

Cancer as a "we-disease": Examining the process of coping from a relational perspective.

Abstract: This paper presents findings on how breast cancer patients and their partners cope together with the cancer diagnosis and treatment. It expands on earlier frameworks of dyadic coping by presenting a model that views dyadic coping as a process that varies according to how couples appraise the illness-related stress, communicate about it, coordinate their coping efforts, and make meaning from the illness experience. Indepth analyses were conducted on interviews with 10 couples who were coping with breast cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
345
0
19

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(400 citation statements)
references
References 35 publications
36
345
0
19
Order By: Relevance
“…This finding supports those of an earlier longitudinal study examining the effect of coping on infertility-related distress, which found a similar gender difference in the pacing and timing of coping with treatment failure (17). Recent studies examining the process of coping with breast cancer have emphasized the need for couples to work together to jointly cope with the illness, and that meaning-based coping can improve dyadic coping efforts (25,26).…”
Section: Discussionsupporting
confidence: 85%
“…This finding supports those of an earlier longitudinal study examining the effect of coping on infertility-related distress, which found a similar gender difference in the pacing and timing of coping with treatment failure (17). Recent studies examining the process of coping with breast cancer have emphasized the need for couples to work together to jointly cope with the illness, and that meaning-based coping can improve dyadic coping efforts (25,26).…”
Section: Discussionsupporting
confidence: 85%
“…Consequently, it is obvious to consider the individual and dyadic coping of the patient in relation to the individual psychological distress, and vice versa. Therefore, cancer can be a stressor concerning both partners simultaneously, and coping with cancer should be viewed as a dyadic affair [20,22]. …”
Section: Dyadic Stress and Copingmentioning
confidence: 99%
“…The omission of the patient's perspective on her husbands' experiences is another limitation. In her review of studies of couples coping with cancer, Kayser et al [42] identifies the 'significant crossover associations between the coping reported by one spouse and the other spouse's adjustment outcomes' (p.405), arguing for research based on the couple as the 'unit of analysis' (p.406). A fuller understanding of the needs of male partners becomes possible when women's perspective on their husbands' needs, psychological and emotional responses and roles and coping strategies are included.…”
Section: Limitationsmentioning
confidence: 97%
“…While there was significant country of origin/cultural diversity in the study sample, culture, as a variable, was not explored. Further research that includes other social factors that may influence the needs of male partners is needed [42].…”
Section: Limitationsmentioning
confidence: 99%